ANALISIS KEBUTUHAN FASILITAS LAMPU PENERANGAN JALAN DI JALUR EVAKUASI JALAN PATENGGANGAN KOTA PADANG - Lucky Muhammad Yuda; Risma Apdeni; Rizky Indra Utama (Teknik Sipil Universitas Negeri Padang, 2023)
Patenggangan Road is one of the roads constructed by the Padang City government as a tsunami evacuation route. This road is a local road with a length of 267 m and a width of 5 m. At night, this road is very dark due to the absence of street lights. This research aimed to analyze the needs for public street lighting facilities on this evacuation route. Data of facility needs were obtained through area observation and measurement, while the analysis was carried out based on SNI 7391:2008 Specifications for Street Lighting in Urban Areas. Analysis and calculation results show that the required number of lamps for street lighting in the study area is 6. The proposed lighting system uses a P-base steel foundation and a single arm steel pipe column with 6 m high. The interval distance between columns is 47 m using a continuous system on the left or right side of the road. The criteria for street lighting used are high pressure mercury gas lamp (MBF/U) with a power of 80 watts and a reflector tilt angle of 15Â°. The lighting strength value is 8.26 lux and the luminance value is 0.65 cd/m2.